English as a foreign language in Saudi Arabia : new insights into teaching and learning English - Moskovsky, Christo; Picard, Michelle, 1970- (Routledge research in language education, 2019)
"English as a Foreign Language in Saudi Arabia : New Insights into Teaching and Learning English offers a detailed discussion of key aspects of teaching and learning English in the Saudi context and offers a comprehensive overview of related research authored or co-authored by Saudi researchers. It provides readers with an understanding of the unique cultural, linguistic, and historical context of English in Saudi Arabia--with a focus on the principal factors that may influence successful teaching and learning of English in this country. Uniquely, the book looks separately at issues pertaining to in-country English learning and learners, and those pertaining to in-country English teaching and teachers. The volume also explores issues concerning Saudi learners and teachers in overseas contexts. Lastly, the book touches on the future of English as a Foreign Language and TESOL in Saudi Arabia and its implications for the field"--